THE BALANCE BETWEEN THEORY AND PRAXIS IN SOUTH AFRICAN PENTECOSTALISM: PATMOS BIBLE SCHOOL AS A MODEL - M.S. Kgatle (Acta Theologica)
Recent developments within South African Pentecostalism reveal that a number of pastors in new Prophetic Churches abuse religion and women and engage in other extreme practices of religion. The vast majority of scholars have linked these recent developments with the gap that exists between theory and praxis in South African Pentecostalism. This article bridges the gap by using Patmos, a Bible School started by Elias Letwaba, one of the first Black workers in the Apostolic Faith Mission (AFM) of South Africa, as a model. Patmos Bible School was an African institution located in Africa for African people. The Bible School offers relevant content to its students, provides specific training for lay preachers and community service, in addition to academic responsibilities. Patmos Bible School thus serves as a model for synergy between theory and praxis in South African Pentecostalism because of its relevant theological curriculum, embracement of African identity, and African indigenous knowledge.